2013
DOI: 10.1007/s10815-013-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronological age vs biological age: an age-related normogram for antral follicle count, FSH and anti-Mullerian hormone

Abstract: ObjectiveTo evaluate the correlation between chronological and biological age by comparing the normograms of AFC, AMH, and FSH.DesignRetrospective studySettingData were taken from patients who visited the Infertility Clinic at Dr. Cipto Mangunkusumo General Hospital Jakarta, Indonesia, between January 2008 and December 2010.Patient(s)Infertile women who visited the Infertility Clinic.Intervention(s)None.Main Outcome Measure(s)Normogram of AFC (n = 366), AMH (n = 1616) and FSH (n = 415).Result(s)The correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 20 publications
7
28
0
4
Order By: Relevance
“…Taking the opposite view, this research maintains that ‘inaccuracy’, i.e., the difference between CA and BA, is a repercussion of individual variations in longevity as well as individual differences in the onset and variations in the aging processes due to genetic, epigenetic, and environmental conditions (Bae et al, ; Belsky et al, ; Cho, Park, & Lim, ; de Rooij & Roseboom, ; Levine, ). Indeed, research in living populations found the estimated standard deviation of the difference between CA and BA varies between three and 10 years (Belsky et al, ; Hochschild, ; Klemera & Doubal, ), and because the health of individuals is highly heterogeneous, as is the rate of aging, discordances between BA and CA can take place from a young age (Belsky et al, ; Molinari, Gasser, & Largo, ; Wiweko et al, ) not just among older individuals as is often assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the opposite view, this research maintains that ‘inaccuracy’, i.e., the difference between CA and BA, is a repercussion of individual variations in longevity as well as individual differences in the onset and variations in the aging processes due to genetic, epigenetic, and environmental conditions (Bae et al, ; Belsky et al, ; Cho, Park, & Lim, ; de Rooij & Roseboom, ; Levine, ). Indeed, research in living populations found the estimated standard deviation of the difference between CA and BA varies between three and 10 years (Belsky et al, ; Hochschild, ; Klemera & Doubal, ), and because the health of individuals is highly heterogeneous, as is the rate of aging, discordances between BA and CA can take place from a young age (Belsky et al, ; Molinari, Gasser, & Largo, ; Wiweko et al, ) not just among older individuals as is often assumed.…”
Section: Introductionmentioning
confidence: 99%
“…However, our research did not find that these two variables acted as a single variable to significantly assess ovarian function. Serum AMH and AFC begin to decline in women between 34 and 35 years old, and AMH predicts biological age earlier than FSH or AFC do, and AFC does so earlier than FSH does [17]. By age 32, over 50% of women with subfertility had AMH levels categorized as "low fertility" (AMH ≤ 19.5 pmol/liter), a figure that increased to 75% by age 39, with a decrease in mean AMH of 1.72 pmol/liter/year [18].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies [17][18][19][20][21] have discussed how AFC and AMH could be used to assess ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a number of published age-specific reference ranges for AMH assayed by manual ELISA in Chinese 23,24 as well as other populations, 14,15,[25][26][27] few are available for the automated assays. Some are available for another automated assay platform manufactured by Roche Diagnostics, 28,29 but as numerical values generated from the two automated platforms are non-equivalent, it would be necessary to establish one specifically for the Access AMH assay.…”
Section: Interpretationsmentioning
confidence: 99%